Russian Folk Culture in the 20 th Century: Oral Evidence of the Villagers (On the Materials of Folklore Expeditions) - Ekaterina A. Dorokhova; Olga A. Pashina (Studia Litterarum)
Folk culture is capable of developing certain adaptation mechanisms that help it promptly react to the changing conditions of natural, socio-political, and economic environment. This is evidenced by the stories of the villagers recorded during folklore expeditions to different regions of Russia. The article highlights changes that took place in the traditional Russian culture under the influence of collectivization in the 1920s–1930s, the collapse of kolkhozes in the 1990s, the development of the rural club amateur performances in the Soviet time, the events of the World War II, modern military conflicts, and Chernobyl ecological catastrophe. The authors come to conclusion that representatives of traditional culture flexibly adapt to their new living conditions, while extreme conditions such as wars and ecological catastrophes often contribute to the actualization of folk culture and enable the return of its certain aspects to living practice.